**k**^2 - 3k = 28**k**^2 - 3k - 28 = 0 (**k**- 7)(**k**+ 4) = 0**k**= -4, 7 and if you're asked to find x:**k**= -4: -4 = (x + 3)/(x - 4) -4(x - 4) = x + 3 -4x + 16 = x + 3 16 - 3 = x...2 Answers · Science & Mathematics · 18/08/2019

...you're given Ea and two temps and asked to calc

**k**.. .. . .whenever you read Ea, T and**k**(or rate) in the same equation...2 Answers · Science & Mathematics · 01/06/2020

... SOLUTION: I like to use this notation: C(n,

**k**) = n! / [(n -**k**)!**k**!] That would mean: C(n, n -**k**) = n! / [(n...;--> {A, B, C} So C(n,**k**) = C(n, n-**k**)6 Answers · Science & Mathematics · 12/09/2019

... tangent lines of form y = 6x +

**k**have slope 6 Set slope dy/dx = 7/[2√(x)] = 6 x = 49... how that applies here (y/7)^2 = x = (y –**k**)/6 6y^2 = 49y – 49**k**6y^2 - 49y + 49**k**= 0 49*49 = 4*6*49**k**...3 Answers · Science & Mathematics · 29/01/2020

If you treat i, j, and

**k**as constants, you have two variables and two unknowns that...39;s solve the first equation for u in terms of v: u + 4v = 4i -**k**u = 4i -**k**- 4v Now substitute that into the other equation and solve for v: 4u...2 Answers · Science & Mathematics · 12/06/2020

You want to

**k**now the values of**k**that ma**k**es x have four solutions. |(x - 4)² - 12| =**k**...12 = ±**k**Now we can add 12 to both sides: (x - 4)² = 12 ±**k**Get the square root of both sides (another ± gets added...1 Answers · Science & Mathematics · 23/07/2020

...question. Notice that the question says, "for what *values* of

**k**..." You did what most people know to do which is to use the...3 Answers · Science & Mathematics · 01/11/2019

**K**-pop has nothing to do with music. I'm not sure what the attraction is but it isn't the music.2 Answers · Entertainment & Music · 06/09/2019

Hint: Let u =

**k**-9. Then write all as an expression as u. Then let u=**k**. Show ur steps if need be and we can ta**k**e it from there.3 Answers · Science & Mathematics · 13/11/2019

f = 1/(2 * π) * √(

**k**/m) The first step is solve problem 20 to determine the spring constant... to determine the increase of the length. ∆ L = 0.15 – 0.10 = 0.05 meter**k**= 4 ÷ 0.05 = 80 N/m Now we can use the spring constant to calculate the...2 Answers · Science & Mathematics · 16/08/2019